Pengaruh Faktor Internal dan Eksternal Terhadap Harga Saham Subsektor Semen - Ayu Rizky Yuniar; Pradana Jati Kusuma; Maria Safitri; Fakhmi Zakaria (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study examines the determinants of share prices of companies in the cement sub-sector on the Indonesia Stock Exchange (IDX), focusing on internal and external factors during the period 2020–2024. The internal factors analysed include the Debt to Equity Ratio (DER), Current Ratio (CR), and company age (AGE), while external factors include interest rates and Gross Domestic Product (GDP). The research method used is a quantitative approach based on secondary data sourced from the IDX, companies' annual financial reports, and statistical data released by the Central Statistics Agency (BPS). The research sample includes six cement sub-sector companies determined through purposive sampling, resulting in 120 quarterly panel data observations. The assessment was conducted using panel data regression with a Fixed Effect Model (FEM) selected from the Chow test and Hausman test, supported by classical assumption testing and hypothesis testing. The results of the study reveal that all independent variables simultaneously have a significant effect on stock prices. Individually, CR has a positive and significant effect, while AGE has a negative and significant effect on stock prices. Meanwhile, DER and interest rates produce an insignificant negative relationship, and GDP has a positive but insignificant effect. This study reveals that the movement of cement sub-sector stock prices can be explained by the interaction of internal and external factors, with liquidity and company age as the main determinants in conditions of overcapacity and macroeconomic uncertainty.